Development of Professional Competences of teachers and Psychologists in the Conditions of Joint training - I. A. Korobeinikov; T. V. Kuzmicheva (Высшее образование в России)
The article presents the results of an experiment to create a model of joint training of students studying on the programs 44.03.01 “Teacher education” and 44.03.03 “Special (defectological) education” at the university. The goal of such educational integration was to ensure the effective interaction of future professionals in these areas in the process of psychological and pedagogical support of schoolchildren with developmental delay who are studying in the conditions of inclusive or integrated environment. Traditional (separate) training of primary education teachers and special psychologists does not allow them to implement properly their professional competencies which are formed within autonomous educational approaches impeding productive cooperation in the context of modern educational practice.The experimental model of joint training of teachers of primary education and special psychologists has been being piloted at Murmansk Arctic State University for several years. The subject field is monitoring of individual development of primary school-age children with developmental delay. The quality of joint training was evaluated in the third and fourth grade curriculum. We assessed the development of cognitive and practical components of professional competences. On the whole the experiment involved 35 future teachers and 35 future special psychologists, 15 professors and 30 workers of educational institutions. The sampling consisted of the full-time students of 2010-2011 enrollment who were selected in two groups – control and experimental. The dynamics of the formation of professional competences was assessed according to the same parameters and we used a large number of diagnostic tests for interim and final evaluation. On the whole the experiment has been organized as a longitude study. During the experiment we have got 280 products of students’ work, which became the base to provide the rationale for the conclusion that joint training of future teachers of primary education and special psychologists has obvious advantages in comparison with the traditional model of students’ training. The professional competences demonstrated by the students of the experimental group were sufficient for providing an adequate psychological and pedagogical support of schoolchildren with developmental delay studying in the conditions of inclusive or integrated environment.